Hemp fiber reinforced lightweight concrete (HRLWC) with coarse pumice aggregate and mitigation of degradation - Merve Tuncer, H.; Canan Girgin, Z. (SPRINGER, 2023)
Concrete with cellulosic fibers should preserve the microstructural and functional properties with less degradation and without micro-organisms for several years. This study focuses on the usability of hemp fibers in a mixture combined with lightweight aggregates (LWA) and cementitious materials. Unlike mostly mortar based current literature, this study addresses the hemp fiber reinforced lightweight concrete (HRLWC) in which coarse aggregates are also used, and these aggregates are volcanic pumice aggregates (VPA). In order to mitigate fiber degradation induced by alkali attack, supplementary cementitious materials (SCM) e.g. metakaolin, blast furnace slag and fly ash were used. Total binding materials and water to binder ratio were taken constant, and the hemp fiber ratio was chosen as V-f = 1.0%. In this scope, compressive strength, flexural behavior, energy absorption, crack width, density, and water absorption were experimentally investigated. Herein, two important exposures on samples are under consideration, one is the natural moisture curing due to LWAs which resemble water reservoir gradually releasing water, the first time for cellulosic fibers in the current literature. The second one is the accelerated aging test to provoke alkali release by immersing in hot water for 10 days. The findings from test results and micro photographs reveal that the pumice aggregates combined with proper SCMs are suitable to contribute sustainable HRLWC design.
Keywords: Hemp; Cellulosic fibers; Pumice; LWA; SCM; HRLWC; MECHANICAL-PROPERTIES; CHEMICAL TREATMENTS; NATURAL FIBER; CEMENT; STRENGTH; DURABILITY; METAKAOLIN; MATRIX; Construction & Building Technology; Engineering; Materials Science